Psychological risks in adolescents in povertyin a Peruvian jungle town - Vega Montoya, Yndolina (2020)
The objective of this work is to determine the relationships of the psychological risk variables: life satisfaction, self-esteem, achievement motivation and future expectations of adolescents from a Peruvian jungle town who live in poverty. The methodology is based on a cross-sectional study, where relative and absolute frequencies were deduced, in the same way measures of central tendency and dispersion, thus the relationships of the variables were also analyzed through Pearson's Chi square with a reliability of 95%. The adolescents involved in the study had a mean age of 14 years, the majority 69 (53.5%) were male and 37 (28.7%) without schooling. Also, 102 (79.1%) reported low life satisfaction, 68 (52.7%) low self-esteem, 90 (69.8%) low achievement motivation, and 86 (66.7) low future expectations. A significant relationship was found between the variables sex (p = .011) and life satisfaction (p = .054) with future expectations. Likewise, future expectations were related to life satisfaction (p = .054) and self-esteem was related to achievement motivation (p = .004). In conclusion, All the psychological risk variables report a high prevalence of the low level, sex and not having schooling have a significant influence, reinforced by the condition of poverty in which they live. It is necessary to promote the psychological health care of this population through the implementation of the community mental health service in the Peruvian jungle.